The Effects of Isometric Fatigue on Trunk Muscle Stiffness: Implications for Shear-Wave Elastography Measurements - Rok Vatovec; Žiga Kozinc; Matej Voglar (Sensors, 2022)
Muscle stiffness has been implicated as a possible factor in low back pain risk. There are few studies on the effects of isometric fatigue on the shear modulus of trunk muscles. This study aimed to investigate the effects of trunk isometric fatigue on the passive and active (during low and high-level contractions) shear moduli of the erector spinae (ES) and superficial and deep multifidus (MF) muscles. We assessed passive and active shear modulus using shear-wave elastography in healthy young participants (n = 22; 11 males, 11 females), before and after an isometric trunk extension fatigue protocol. Maximal voluntary force decreased from 771.2 ± 249.8 N before fatigue to 707.3 ± 204.1 N after fatigue (−8.64%; p = 0.003). Passive shear modulus was significantly decreased after fatigue in the MF muscle (p = 0.006–0.022; Cohen’s d = 0.40–46), but not the ES muscle (p = 0.867). Active shear modulus during low-level contraction was not affected by fatigue (p = 0.697–0.701), while it was decreased during high-level contraction for both muscles (p = 0.011; d = 0.29–0.34). Sex-specific analysis indicated the decrease in ES shear modulus was significant in males (p = 0.015; d = 0.31), but not in females (p = 0.140). Conversely, the shear modulus in superficial MF had a statistically significant decrease in females (p = 0.002; d = 0.74) but not in males (p = 0.368). These results have important implications for further investigations of the mechanistic interaction between physical workloads, sex, muscle stiffness (and other variables affecting trunk stability and neuromuscular control), and the development/persistence of low back pain.